Technologies for CMOM Activities in Wastewater Collection Systems : WEF special publication - McLamarrah, Jane; McLamarrah, Jane (Water Environment Federation, 2022)
Many wastewater collection system operators have successfully adopted capacity, management, operations, and maintenance (CMOM) activities to move from reactive operation and maintenance (O&M) to more proactive O&M activities. This publication identifies technologies that can be applied to further this movement into more preventive and even predictive O&M activities and continue to reduce reactive O&M. The publication is particularly useful for supervisors, operators, and maintenance personnel. The increased use of innovative technology, smart data, system optimization, and real-time controls will enhance optimization of O&M budgets and contribute to an overall reduction in life-cycle costs.